A Note on Rising Food Prices - Mitchell, Donald (World Bank, Washington, DC, 2012)
The rapid rise in food prices has been a burden on the poor in developing countries, who spend roughly half of their household incomes on food. This paper examines the factors behind the rapid increase in internationally traded food prices since 2002 and estimates the contribution of various factors such as the increased production of biofuels from food grains and oilseeds, the weak dollar, and the increase in food production costs due to higher energy prices. It concludes that the most important factor was the large increase in biofuels production in the U.S. and the EU. Without these increases, global wheat and maize stocks would not have declined appreciably, oilseed prices would not have tripled, and price increases due to other factors, such as droughts, would have been more moderate. Recent export bans and speculative activities would probably not have occurred because they were largely responses to rising prices. While it is difficult to compare the results of this study with those of other studies due to differences in methodologies, time periods and prices considered, many other studies have also recognized biofuels production as a major driver of food prices. The contribution of biofuels to the rise in food prices raises an important policy issue, since much of the increase was due to EU and U.S. government policies that provided incentives to biofuels production, and biofuels policies which subsidize production need to be reconsidered in light of their impact on food prices.